Sustainable Tourism Development in Essaouira - Bozsik, Norbert; Mourabite, Sara El (Afrika Tanulmányok / Hungarian Journal of African Studies, 2023)
Tourism is an important part of the global economy and culture. However, the tourism sector accounts for 8% of global greenhouse gas emissions. This is why it is imperative to move towards a more sustainable tourism model. Developing countries consider tourism as an essential element for economic development and poverty alleviation. The aim of the research was to reveal the development of sustainable tourism in Essaouira, specifically. We conducted research by gathering data and developing a series of questionnaires. Our sample design, known as simple random sampling, ensured that every item in the population had an equal opportunity to be included in the sample and any possible sample. Essaouira, as a city in the developing country of Morocco, tourism plays an important role in economic growth, and has become a popular tourist destination. Sustainable development is needed in order to increase the length of stay of tourists; therefore, it is necessary to behave responsibly and ethically towards nature. This is also important because certain tourist activities have negative impacts on Essaouira’s environment. Apart from the local population and tourists, the local government should also take a more active role in creating sustainability. The properly chosen marketing policy of tourist organizations can also make tourism more sustainable in Essaouira. Besides, tourism organizations and tourism-related companies should develop sustainable products.